A novel Caldicott-compliant hospital imaging protocol for open fracture photography. (2020) - Houston, James; Ashby, Luke; Ogidi, Jonathan; Lui, Daren F; Trompeter, Alex J
Abstract : Open fractures incur significant morbidity and mortality, and as such have standardised guidelines for their management. Photography of open fractures is an essential component of documentation in the treatment of open fractures as per the British Orthopaedic Association Standards of Trauma and National Institute for Health and Care Excellence guidelines. Smartphones have made photography easily accessible to the clinician, but serious concerns exist regarding data security and the consent process around the use of sensitive clinical images. This project sought to overcome this issue by developing a Caldicott-compliant hospital imaging protocol that allows clinicians to use their smartphone to upload open fracture images into the patient's permanent record. Implementation of the protocol was audited and resulted in the increase of safe and secure open fracture photographic storage to inpatient medical records. This protocol would be transferrable to other hospital trusts and could be adopted across major trauma networks.